Quantitative sensory testing profiles in children, adolescents and young adults (6–20 years) with cerebral palsy: Hints for a neuropathic genesis of pain syndromes. (May 2018) - Blankenburg, M.; Junker, J.; Hirschfeld, G.; Michel, E.; Aksu, F.; Wager, J.; Zernikow, B.
Abstract: Introduction: Many patients with cerebral palsy (CP) suffer chronic pain as one of the most limiting factors in their quality of life. In CP patients, pain mechanisms are not well understood, and pain therapy remains a challenge. Quantitative sensory testing (QST) might provide unique information about the functional status of the somatosensory system and therefore better guide pain treatment. Objectives: To understand better the underlying pain mechanisms in pediatric CP patients, we aimed to assess clinical and pain parameters, as well as QST profiles, which were matched to the patients' cerebral imaging pathology. Patients and methods: Thirty CP patients aged 6–20 years old (mean age 12 years) without intellectual impairment underwent standardized assessments of QST. Cerebral imaging was reassessed. QST results were compared to age- and sex-matched controls (multiple linear regression; Fisher's exact test; linear correlation analysis). Results: CP patients were less sensitive to all mechanical and thermal stimuli than healthy controls but more sensitive to all mechanical pain stimuli (each p < 0.001). Fifty percent of CP patients showed a combination of mechanical hypoesthesia, thermal hypoesthesia and mechanical hyperalgesia; 67% of CP patients had periventricular leukomalacia (PVL), which was correlated with mechanic (r = 0.661; p < 0.001) and thermal (r = 0.624; p = 0.001) hypoesthesia. Conclusion: The combination of mechanical hypoesthesia, thermal hypoesthesia and mechanical hyperalgesia in our CP patients implicates lemniscal and extralemniscal neuron dysfunction in the thalamus region, likely due to PVL. We suspect that extralemniscal tracts are involved in the original of pain in our CP patients, as in adults. Highlights: Hyperalgesia was combined with hypoesthesia in CP patients with chronic pain. Hyperalgesia correlates with periventricular leukomalacia in CP patients. Results implicates lemniscal and extralemniscal neuron dysfunction due to PVL. Results implicates extralemniscal tracts involvement in the origin of pain.